2016
DOI: 10.1080/10934529.2016.1212556
|View full text |Cite
|
Sign up to set email alerts
|

Settlement behavior of municipal solid waste due to internal and external environmental factors in a lysimeter

Abstract: Long-term settlement magnitude is influenced by changes in external and internal factors that control the microbiological activity in the landfill waste body. To improve the understanding of settlement phenomena, it is instructive to study lysimeters filled with MSW. This paper aims to understand the settlement behavior of MSW by correlating internal and external factors that influence waste biodegradation in a lysimeter. Thus, a lysimeter was built, instrumented and filled with MSW from the city of Campina Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In the long-term scenarios, the main issue appears as a loss of waste matter caused by biodegradation of organic waste (OW) compounds of which the mechanical consequences have not been fully investigated yet [ 4 ]. Landfill settlements are generally defined as a vertical displacement of the waste body due to MSW compression, rearrangement of the particles, and biological degradation of the MSW organic matter (OM) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the long-term scenarios, the main issue appears as a loss of waste matter caused by biodegradation of organic waste (OW) compounds of which the mechanical consequences have not been fully investigated yet [ 4 ]. Landfill settlements are generally defined as a vertical displacement of the waste body due to MSW compression, rearrangement of the particles, and biological degradation of the MSW organic matter (OM) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies from Brazil [ 5 ] showed that settlement behaviour of MSW due to internal and external environmental factors can be simulated by an experiment performed in a lysimeter. Moreover, cited authors revealed that the interpretation of factors determining the range of landfill settlements can be enhanced with the application of statistical tools such as descriptive analysis and principal component analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sutthasil et al (2014) [28] compared solid waste stabilisation and methane emissions from anaerobic and semi-aerobic landfills operating under tropical conditions. Araujo et al (2017) [29] statistically modelled an MSW settlement with a lysimeter, while Melo et al (2016) [30] examined the settlement behaviour of MSW according to the internal/external environmental factors in a lysimeter.…”
Section: Introductionmentioning
confidence: 99%